Polynomial methods for component matching and verification - Smith, James; De Micheli, Giovanni (Digest of technical papers - IEEE/ACM International Conference on Computer-Aided Design, 1998)
Component reuse requires designers to determine whether or not an existing component implements desired functionality. If a common structure is used to represent components that are described at multiple levels of abstraction, comparisons between circuit specifications and a library of potential implementations can be performed quickly. A mechanism is presented for compactly specifying circuit functionality as polynomials at the word level. Polynomials can be used to represent circuits that are described at the bit level or arithmetically. Furthermore, in representing components as polynomials, differences in precision between potential implementations can be detected and quantified.